2004
DOI: 10.12968/ijpn.2004.10.1.12013
|View full text |Cite
|
Sign up to set email alerts
|

The Abbey pain scale: a 1-minute numerical indicator for people with end-stage dementia

Abstract: The need for a specialized clinical regimen for patients with dementia who require palliative care has only recently been recognized. Structured approaches to palliative care are not well developed. The recognition and treatment of pain is an important part of this management risk. However, pain is consistently underdiagnosed and undertreated in this population. A factor contributing to this has been a lack of appropriate tools to help recognize and document pain. This study sought to develop and validate an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
294
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(301 citation statements)
references
References 12 publications
1
294
0
6
Order By: Relevance
“…at home care and hospice care). Six studies included direct evidence from people with dementia (The Anne Mei, 2002;Allen, 2003;Abbey et al, 2004;Shega et al, 2004;Magaziner et al, 2005;Abbey, 2006) as opposed to relying on family carers' and health professionals' accounts and/or records of the care. Most studies had purposive or convenience samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…at home care and hospice care). Six studies included direct evidence from people with dementia (The Anne Mei, 2002;Allen, 2003;Abbey et al, 2004;Shega et al, 2004;Magaziner et al, 2005;Abbey, 2006) as opposed to relying on family carers' and health professionals' accounts and/or records of the care. Most studies had purposive or convenience samples.…”
Section: Resultsmentioning
confidence: 99%
“…Nonpharmaceutical interventions were effective in reducing discomfort for 62% of participants, and analgesics effective for 75% of participants The study demonstrated more effective use of analgesia and less discomfort in the intervention group. This work, and that of Abbey et al (2004), highlighted the importance of structured ways of working that combine educational support for care workers with the development of interventions that are specific for end-of-life care for people with dementia. These studies were based in nursing homes and relied on effective cross-disciplinary working.…”
Section: Palliative Symptom Management For People With Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…The APS recommended Abbey Pain Scale is a 4-point scale that is used to rate six domains of observation: vocalisations, facial expressions, body language, behavioural changes, physiological changes and physical changes. 24 This and other pain measures appropriate for this population are published in Pain in Residential Aged Care Facilities: Management Strategies. 18 …”
Section: Discussionmentioning
confidence: 99%
“…In the global literature, 12 instruments were found proposing the evaluation of pain in people with severe dementia published until 2013, being those: Abbey Pain Scale (8) ; CNPI -Checklist of Nonverbal Pain Behaviors (9) , CPAT -Certified Nursing Assistant Pain Assessment Tool (10) ; DOLOPLUS-2 (11) ; MPS -Mahoney Pain Scale (12) ; MOBIDMobilization-Observation-Behavior-Intensity-Dementia Pain Scale (13) e MOBID-2 (14) ; NOPPAIN -Non-communicative Patient's Pain Assessment Instrument (15) ; PACS-LAC -Pain Assessment Checklist for Seniors With Limited Ability to Communicate (16); PADE -Pain Assessment for the Dementing Elderly (17) ; PAINAD -Pain Assessment in Advanced Dementia (18) , PAINE -Pain Assessment in Non communicative Elderly Persons (19) and ADD -Assessment of Discomfort in Dementia (20) .…”
Section: Introductionmentioning
confidence: 99%